2021
DOI: 10.37433/aad.v2i1.79
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of COVID-19 on school-based agricultural education teachers in the U.S.

Abstract: The COVID-19 pandemic of 2020 disrupted education all over the world. Teachers and students were forced to adapt to online learning. In the U.S., school-based agricultural education (SBAE) teachers faced challenges in delivering what is traditionally a hands-on curriculum. This study used a Pedagogical Design Capacity framework to understand the experiences of four SBAE teachers at different career stages and different geographic regions of the U.S. Our results showed dissatisfaction over initial changes, frus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…As teachers addressed challenges due to the COVID-19 pandemic in both their personal and professional lives (WHO, 2021), the modality of instruction had strong impacts on self-efficacy (Cohen's d = 0.79). The results in this study align with previous research that identified challenges teachers faced at the onset of the pandemic, including changes in teaching approaches, educational experiences, and teacher well-being (Easterly et al, 2021). Cardullo et al (2021) identified factors such as perceived usefulness and system quality as predictors for teacher self-efficacy, or the belief that teachers can successfully motivate students while teaching online.…”
Section: Conclusion Discussion and Recommendationssupporting
confidence: 86%
See 3 more Smart Citations
“…As teachers addressed challenges due to the COVID-19 pandemic in both their personal and professional lives (WHO, 2021), the modality of instruction had strong impacts on self-efficacy (Cohen's d = 0.79). The results in this study align with previous research that identified challenges teachers faced at the onset of the pandemic, including changes in teaching approaches, educational experiences, and teacher well-being (Easterly et al, 2021). Cardullo et al (2021) identified factors such as perceived usefulness and system quality as predictors for teacher self-efficacy, or the belief that teachers can successfully motivate students while teaching online.…”
Section: Conclusion Discussion and Recommendationssupporting
confidence: 86%
“…The most powerful of these experiences included mastery experiences, by which an individual finds success in attempting a given behavior, and in turn be more likely to attempt the behavior again, ultimately finding themselves successful (Bandura, 1986). In the case of online learning, the frustrations shared by teachers presents a hurdle for mastery experience to occur (Cardulla et al, 2021;Easterly et al, 2021). Additionally, vicarious experiences provide the opportunity for observation of others and their success in completing a given behavior.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies where synchronous live video lessons were used, instances of engagement were found in more than double the number of studies than instances of disengagement. The use of breakout rooms for students to work together in groups was particularly engaging (Education Scotland, 2021) and interactive approaches for social online meetings, such as scavenger hunts and trivia were particularly popular (Easterly et al, 2021). Allowing students to use the chat function within live lessons also promoted peer interaction and peer teaching (Hodgen et al, 2020), as did providing social time at the beginning and end of lessons for students to catch up with each other in a more informal setting (Lepp et al, 2021).…”
Section: The Role Of Live Synchronous Lessons On Student Engagementmentioning
confidence: 99%